Strength training - Brown, Lee E. 1956- (Human Kinetics, 2007)
Whether you're launching a lifting program or fine-tuning a serious fitness regimen, Strength Training will fill any knowledge void and correct misconceptions to ensure proper technique, safety, and progressions. Multiple program options for specific machines, free weights, and other apparatuses provide the flexibility to tailor your training to personal preferences and needs.